Shared socioeconomic pathways (SSPS) and projected changes in temperature and rainfall: A case study of the Western Province of Sri Lanka - Piratheeparajah, N.; Dinusha Maduwanthi, S. (Shahid Beheshti University, 2025)
The Western Province, as the country's principal province, is confronting many challenges prompted by climate change. The repercussions of climate-related phenomena in the Western Province obstruct the overall advancement of Sri Lanka. Consequently, it is imperative to comprehend future climate change trajectories through climate projections. This study endeavors to discern alterations in temperature and precipitation patterns in the Western Province from 2020 to 2100 based on varying Shared Socioeconomic Pathways (SSP) 2-4.5 and 5-8.5 and to propose suitable mitigation strategies. The research utilizes data sourced from the World Bank's Climate Change Knowledge Portal (CCKP) and various government and non-governmental organizations, including the Department of Meteorology, employing descriptive analysis. The findings suggest that the average temperature in the Western Province is anticipated to increase by 1.20°C under SSP2-4.5 and 1.95°C under SSP5-8.5 from 2020 to 2100. Likewise, the annual rainfall is projected to rise by 175.48mm under SSP2 4.5 and 209.78mm under SSP5-8.5. Furthermore, the study indicates that a decline in monthly rainfall coupled with an upsurge in temperature is foreseen in the Western Province as it transitions from SSP2-4.5 to SSP5-8.5 concerning carbon emissions. Thus, it is preferable to maintain carbon emissions closer to SSP2-4.5 rather than SSP5-8.5. Additionally, it is crucial to implement development projects that take into account anticipated future changes in temperature and rainfall.
Keywords: Changes; Projections; Rainfall; Temperature; Western province